The Effectiveness of Safety Star Grading (SSG) in Improving Compliance of ICOP RTA 2010 among Express Bus Operators - W. Ameer Batcha; M.S. Ahmad; N.K. Alias; I. Othman; A.H. Ariffin (Journal of the Society of Automotive Engineers Malaysia, 2022)
Occupational Safety and Health Industry Code of Practice for Road Transport Activities 2010 (ICOP RTA 2010) was introduced in Malaysia in 2010 as a gazette under the Occupational Safety and Health Act 1994 (OSHA 1994). This initiative objectively was to improve the safety and health of the transportation sector. Since the introduction of ICOP RTA 2010, MIROS had conducted a Safety, Health, and Environment (SHE) Audit on bus and fleet operators to assess the compliance level of ICOP RTA 2010 among operators. Later, in 2013, MIROS introduced Safety Star Grading (SSG) which is a voluntary program focused to express bus operators. The main purpose of SSG is to improve the level of safety and health in the public transportation sector. Thus, this paper aims to explore the effectiveness of SSG in improving the compliance of ICOP RTA 2010 among selected express bus operators. The study shows that compliance to ICOP RTA 2010 increased by 15% among the assessed express bus operators after the implementation of Safety Star Grading (SSG). Hence, the findings reflected that SSG act as a support program to motivate express bus operator in compliance with ICOP RTA 2010.